Measurement of pitch perception as a function of cochlear implant electrode and its effect on speech perception with different frequency allocations. - Grasmeder, M. L.; Verschuur, C. A.; van Besouw, R. M.; Wheatley, A. M. H.; Newman, T. A. (International Journal of Audiology, 2019)
Objective: An experiment was conducted to investigate the possibility that speech perception could be improved for some cochlear implant (CI) users by adjustment of the frequency allocation to the electrodes, following assessment of pitch perception along the electrode array. Study sample: Thirteen adult CI users with MED-EL devices participated in the study. Design: Pitch perception was assessed for individual CI electrode pairs using the Pitch Contour Test (PCT), giving information on pitch discrimination and pitch ranking for adjacent electrodes. Sentence perception in noise was also assessed with ten different frequency allocations, including the default. Results: Pitch perception was found to be poorer for both discrimination and ranking scores at either end of the electrode array. A significant effect of frequency allocation was found for sentence scores [F(4.24,38.2) = 7.14, p < 0.001] and a significant interaction between sentence score and PCT ranking score for basal electrodes was found [F(4.24,38.2) = 2.95, p = 0.03]. Participants with poorer pitch perception at the basal end had poorer scores for some allocations with greater basal shift. Conclusions: The results suggest that speech perception could be improved for CI users by assessment of pitch perception using the PCT and subsequent adjustment of pitch-related stimulation parameters.